2021
DOI: 10.1097/meg.0000000000002107
|View full text |Cite
|
Sign up to set email alerts
|

Population-based incidence and prevalence of inflammatory bowel diseases in Milan (Northern Italy), and estimates for Italy

Abstract: Objective A reliable measure of the burden of inflammatory bowel diseases (IBDs), including ulcerative colitis and Crohn’s disease, are essential to monitor their epidemiology and plan appropriate health services. Methods This is a population-based study carried out in the Milan Agency for Health Protection. Incident and prevalent cases were identified according to specific codes in hospital discharges and copayment exemptions. Age-standardized incidence rates were computed for 2015–2018 and yearly rates fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 27 publications
2
7
2
Order By: Relevance
“…Despite some degree of variability, our data are in agreement with the results of previous epidemiologic studies carried out in Italy [ 5 , 6 , 7 , 8 , 9 ]. In particular, a previous Italian epidemiologic study carried out in the Barletta-Andria-Trani Province of the Apulia region, found an IBD prevalence of 187.2/100,000 (95% CI: 160.6–217.0) and an incidence of 16.2/100,000 (95% CI 12.5–20.7) per year [ 17 ]; taking into account that these data were published in 2013, they are consistent with our findings of an increase in IBD prevalence and incidence.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Despite some degree of variability, our data are in agreement with the results of previous epidemiologic studies carried out in Italy [ 5 , 6 , 7 , 8 , 9 ]. In particular, a previous Italian epidemiologic study carried out in the Barletta-Andria-Trani Province of the Apulia region, found an IBD prevalence of 187.2/100,000 (95% CI: 160.6–217.0) and an incidence of 16.2/100,000 (95% CI 12.5–20.7) per year [ 17 ]; taking into account that these data were published in 2013, they are consistent with our findings of an increase in IBD prevalence and incidence.…”
Section: Discussionsupporting
confidence: 92%
“…However, local studies published in the last 10 years reported a significantly higher order of magnitude of IBD cases in Italy. The prevalence of IBD ranges from 442 per 100,000 population in the district of Milan (North Italy) to 187 per 100,000 population in Sardinia [ 5 , 6 ], with a lower prevalence of CD compared with UC in the whole country [ 5 , 6 , 7 , 8 , 9 ]. Incidence rates of CD varies from 6.1 to 17.9 per 100,000 population/year for CD and from 12.2 to 15.3 per 100,000 population/year for UC [ 5 , 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Although Southern European countries have often been considered as low prevalent areas for IBD, recent studies have proven this is no longer the case, as can be seen from recent studies from Spain, Italy and Portugal. [12][13][14][15][16][17] Western Europe is vast and disease rates vary not only between countries, but within each country itself. One of the largest UK studies to determine epidemiology rates in IBD explored health records from more than 38.3 million people between 2000 and 2020 and found a population incidence rate of 36 new cases per 100,000 person-years, with greater rates in Scotland and Northern Ireland compared to England and Wales.…”
Section: Incidence and Prevalence Of Ibdmentioning
confidence: 99%
“…Currently, IBD affect a growing number of people worldwide, with more than 6.8 million cases, and the number will increase exponentially over the next decade [ 3 ]. New data suggest that around 0.2% of the European population suffers from IBD at the present time [ 4 ] and approximately 260,000 subjects are affected by IBD in Italy (0.4%) [ 5 ].…”
Section: Introductionmentioning
confidence: 99%